The Emerging Picture of the Roles of CircRNA-CDR1as in Cancer - Jiang, Chaohua; Zeng, Xiaohong; Shan, Renfeng; Wen, Wu; Li, Jianfeng; Tan, Jinfeng; Li, Lei; Wan, Renhua (Frontiers in Cell and Developmental Biology, 2020)
Circular RNAs (circRNAs) are covalently closed circular structures without 5’ caps and 3’ tails, which are mainly formed from precursor mRNAs (pre-mRNAs) via back-splicing of exons. With the development of RNA sequencing and bioinformatic analysis, circRNAs were recently rediscovered and found to be widely expressed in the tree of life. Cerebellar degeneration-related protein 1 antisense RNA (CDR1as) is recognized as one of the most well-identified circRNAs. It contains over 70 miR-7 binding sites and can regulate gene activity by sponging miR-7. Increasing numbers of studies have recently demonstrated that CDR1as is abnormally expressed in many types of tumors, such as colorectal cancer, cholangiocarcinoma and osteosarcoma, and plays a vital role in the development of cancer. However, there are few reviews focusing on CDR1as and cancer. Hence, it is important to review and discuss the role of CDR1as in cancer. Here, we first review the main biological features of CDR1as. We then focus on the expression and roles of CDR1as in cancer. Finally, we summarize what is known on the role of CDR1as in cancer and discuss future prospects in this area of research.